Penerapan terapi non-farmakologi dalam upaya pengendalian tekanan darah pada penderita hipertensi (SEMANGAT SEHAT) - Dekawaty, Ayu; Aditiaya, Aditiaya; Fadhilah, Amirotun; Ningsih, Cahaya Fitri May; Aziza, Dera; Safitri, Indri; Intan, Intan; Astuti, Mega; Yani, Pitri; Abdillah, Ricky Farhan; Saprina, Wahyuni (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Hypertension is a condition of elevated blood pressure that can be influenced by various factors, such as lack of physical activity, an unhealthy diet, and an imbalance in nutritional intake. If left uncontrolled, high blood pressure can increase the risk of cardiovascular complications such as stroke, heart disease, and kidney disorders. Blood pressure control can be achieved through pharmacological and non-pharmacological approaches. One non-pharmacological approach that can be implemented is a combination of physical activity and nutritional interventions, such as the Semangat Sehat Program, which consists of healthy exercise and watermelon juice consumption. Purpose: To provide education on blood pressure control through the implementation of hypertension exercise therapy and watermelon juice consumption in patients with hypertension. Method: This activity was conducted in the 13 Ulu Village, Palembang City, involving 30 participants from the 13 Ulu Village area with hypertension complaints. The goal of this activity was to provide education to increase awareness, motivation, and the implementation of a healthy lifestyle in hypertension management. Education was provided community-based with mentoring and an interactive communication approach. The intervention included hypertension exercise and watermelon juice. Evaluation was conducted by measuring blood pressure before therapy (pre-test) and after therapy (post-test). The results were analyzed to determine the effectiveness of the therapy in controlling blood pressure. Results: Blood pressure measurements from 30 participants before the intervention (pre-test) revealed an average systolic blood pressure of 148 mmHg, with a minimum of 99 mmHg and a maximum of 182 mmHg. Meanwhile, the average diastolic blood pressure was 89.34 mmHg, with a minimum of 66 mmHg and a maximum of 129 mmHg. After the intervention (post-test), the average systolic blood pressure decreased to 136 mmHg, with a minimum of 95 mmHg and a maximum of 168 mmHg. Meanwhile, the average diastolic blood pressure decreased to 83.34 mmHg, with a minimum of 60 mmHg and a maximum of 118 mmHg. Conclusion: Community service activities through the